Memahami Novel Seputih Hati Yang Tercabik Karya Ratu Wadarita Melalui Pendekatan Mimesis: “The White Heart” Novel Throughout By Ratu Wadarita Through The Mimesis Approach - Basuki Sarwo Edi (Kibas Cenderawasih : Jurnal Ilmiah Kebahasaan dan Kesastraan, 2022)
This study aims to describe the mimetic elements of the novel, Seputih Hati, Shredded Mimesis Study by Ratu Wadarita, including: a. social interaction by leading to mimetic reality, b. social contacts that occur in real life, c. the embodiment or imitation of real life, d. Literary works based on the reality of social life experienced, e. Linking literary works to reality. This study uses a descriptive method with a qualitative approach because the data will be taken in words (descriptions). The source of the data in this study is the Novel Seputih Hati that is Torn by Ratu Wadarita. The data collection technique used literature review method. The technique used in this research was content analysis. The research results prove the following points. (1) Domestic Problems (2) Legal Issues (3) Religion as a Guide.